Jordan : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Jordan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Jordan has made significant progress since the 2014 Article IV Consultation but pressing challenges remain. The gradual pick-up in growth from 2010 to 2014 ended in 2015, with real GDP growth decelerating from 2.4 percent in 2015 to 2 percent in 2016. Labor market conditions have remained challenging, particularly for youth and women, with the unemployment rate increasing to 15.8 percent in the second half of 2016. Despite considerable progress and recent improvements, the outlook remains challenging. Real GDP growth is projected to reach 2.3 percent in 2017, while inflation is expected to stabilize at about 2.5 percent by year-end.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet